Risk of acute appendicitis in and around pregnancy: a population-based cohort study from England - Zingone, Fabiana; Sultan, Alyshah Abdul; Humes, David; West, Joe (Lippincott Williams & Wilkins, 2015)
Objective: To determine the absolute and relative risk of acute appendicitis during the antepartum and postpartum periods compared with the time outside pregnancy among women of childbearing age.